Utilisation of common grain crops in Zimbabwe - Chandiposha, Misheck; Chagonda, Ignatius; Makuvaro, Veronica (Academic Journals, 2016)
Grain production in Zimbabwe is very important to food security of the country and therefore should be promoted. Potentially, knowledge on utilisation and value addition of grain crops can be viewed as strong strategies in promoting its production. Value addition results in various products from each grain crop and this may increase utilisation and profitability. In this review paper, an attempt is made to describe the utilisation and value addition of common grain crops to Zimbabwe which include maize, soybeans, wheat, sorghum, groundnuts, pearl millets, bambara nuts and cowpea.